Nanoporous silicon tubes: the role of geometry in nanostructure formation and application to light emitting diodes. (8th June 2017) - Vukajlović Pleština, Jelena; Đerek, Vedran; Francaviglia, Luca; Amaduzzi, Francesca; Potts, Heidi; Ivanda, Mile; Fontcuberta i Morral, Anna
Abstract: Obtaining light emission from silicon has been the holy grail of optoelectronics over the last few decades. One of the most common methods for obtaining light emission from silicon is to reduce it to a nanoscale structure, for example by producing porous silicon. Here, we present a method for the large-area fabrication of porous silicon microtubes by the stain etching of silicon micropillar arrays. We explain and model how the formation of the microtubes is influenced by the morphology of the substrate, especially the concave or convex character of the 3D features. Light emission is demonstrated at the micro- and nanoscale respectively by photo- and cathodoluminescence. Finally, we demonstrate a 0.55 cm 2 device that can work as a photodetector with 2.3% conversion efficiency under one sun illumination, and also as a broadband light emitting diode, illustrating the applicability of our results for optoelectronic applications.